The Efficacy of Letrozole Co-Treatment in an Antagonist Protocol for Women with Polycystic Ovary Syndrome Undergoing IVF: A Retrospective Study - Lin J; Wu F; Zhu Y; Zhu Q; Du T; Lin J (Dove Medical Press, 2024)
Jing Lin,1 Fenglu Wu,2 Yanwen Zhu,2 Qianqian Zhu,2 Tong Du,2 Jiaying Lin2 1Center for Reproductive Medicine, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China; 2Department of Assisted Reproduction, Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of ChinaCorrespondence: Jiaying Lin; Tong Du, Department of Assisted Reproduction, Shanghai Ninth People's Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Zhizaoju Road No. 639, Shanghai, People's Republic of China, Email lemon_1114@126.com; ocyte@qq.comObjective: Our objective was to investigate the efficacy of letrozole co-treatment in an antagonist protocol for infertile women with polycystic ovary syndrome (PCOS).Patients and Methods: This retrospective cohort study included infertile women with PCOS undergoing IVF/ICSI with and without letrozole co-treatment in an antagonist protocol from 2007- 2021 at Shanghai Ninth People's Hospital (Shanghai, China). A total of 1559 participants were enrolled, with 1227 women in the antagonist group and 332 women in the letrozole co-treatment group. Propensity score-based patient-matching model was conducted to balance covariates between the groups. The primary outcome was the number of retrieved oocytes, with secondary outcomes including endocrine parameters, ovarian stimulation outcomes, pregnancy outcomes, and obstetrical and neonatal complications.Results: Letrozole co-treatment induced significant changes in hormonal regulation, increased the percentage of large follicles, and resulted in fewer retrieved oocytes (P < 0.05). However, there was no negative impact on the number of usable embryos or good-quality embryos (P > 0.05). The live birth rates following fresh embryo transfer were comparable between the letrozole and control groups (single embryo transfer: 28.9% vs 29.7%, P > 0.05; double embryo transfer: 37.3% vs 45.6%, P > 0.05). Additionally, there were no significant differences between the two groups in the live birth rate per patient after frozen embryo transfer and the cumulative live birth rate (P > 0.05). No significant differences in obstetrical and neonatal complications were observed between the groups (P > 0.05).Conclusion: The addition of letrozole to the antagonist protocol for women with PCOS undergoing IVF induces a higher percentage of large follicles during oocyte retrieval, while reducing the overall number of retrieved oocytes. Moreover, the use of letrozole demonstrates comparable clinical outcomes following embryo transfers. These findings highlight the potential application of letrozole in an antagonist protocol for women with PCOS.Keywords: letrozole, antagonist protocol, polycystic ovary syndrome, follicle, in vitro fertilization